P649 The impact of COVID-19 on quality of life among patients with inflammatory bowel diseases – A Danish prospective population-based cohort study. (21st January 2022) - Attauabi, M; Dahlerup, J F; Poulsen, A; Hansen, M R; Vester-Andersen, M K; Eraslan, S; Prahm, A P; Pedersen, N; Larsen, L; Jess, T; Neumann, A; Haderslev, K V; et al.
Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic raised concerns among patients with ulcerative colitis (UC) and Crohn's disease (CD) fearing an increased susceptibility to infection and increased risk of poor outcomes. Furthermore, the impact of COVID-19 on subsequent health-related quality of life (HRQoL) has so far not been described. We aimed to evaluate the HRQoL in relation to the severity of COVID-19 in a cohort of survivors. Methods: We conducted a population-based study investigating the outcomes of COVID-19 among patients with UC and CD in Denmark. The Danish COVID-19 IBD Database is an extensive population-based database which prospectively monitors the disease course of laboratory-confirmed COVID-19 among patients with UC and CD. Severe COVID-19 was defined as COVID-19 necessitating intensive care unit admission, ventilator use, or death, while adverse COVID-19 was defined as requirement of COVID-19 related hospitalization. HRQoL was assessed using several validated questionnaires, including the EuroQol five-dimension five-level (EQ-5D-5L) questionnaire, EuroQol Visual Analogue Scale (EQ-VAS), Short Inflammatory Bowel Disease Questionnaire (SIBDQ), IBD Disability Index (IBD-DI), and IBD Fatigue Score. Results: HRQoL after COVID-19 was assessed among 137/319 (42.9%) patients with UC of whom 125 (91.2%) and 12 (8.8%) patients experienced mild and adverse COVID-19, respectively. Furthermore, HRQoL was assessed among 85/197 (43.1%) patients with CD of whom 74 (87.1%) and 11 (12.9%) patients experienced mild and adverse COVID-19, respectively. HRQoL was assessed after a median of 5.1 months (IQR 4.5–7.9) after infection. Baseline characteristics are presented according to the availability of HRQoL data in Table 1. No difference was observed in terms of EQ-5D-5L among patients with UC and CD or patients with mild, adverse, or severe COVID-19 (Table 2). Accordingly, the SIBDQ scores were similar among patients with mild, adverse or severe COVID-19 and UC (mild: median 59 (IQR 50–65), adverse: 62 (54–65), severe: 62 (54–65), p=0.89) or CD (mild: 57 (46–65), 58 (49–64), 58 (49–64), p=0.91) as well, and no difference was observed in the subscores (Table 2). In line with these results, the IBD Disability Index (UC: median 10 (IQR 6–16), CD: 13 (6–20), p= 0.16) were not associated with the severity of COVID-19 (Table 3). Finally, CD patients with adverse COVID-19 experienced more fatigue than patients with mild COVID-19 (26 (IQR 25–35) vs. 41 (IQR 29–46), p= 0.03). Conclusion: This Danish population-based study found no durable impact of COVID-19 on health-related quality of life among patients with inflammatory bowel disease providing further assurance for the clinical guidelines for IBD care during the pandemic.